Triplosphaeria guizhouensis sp. nov. (Tetraplosphaeriaceae, Pleosporales), a novel taxon from freshwater habitat in Guizhou Province, China - Liu, Ling-Ling; Feng, Yao; Wei, Quan-Quan; Zhang, Meng; Gu, Xiao-Feng; Liu, Zuo-Yi; Gou, Jiu-Lan (Phytotaxa, 2023)
During our survey of the taxonomy and diversity of freshwater fungi of Guizhou Province, China, a Tetraploa-like taxon was collected from stream in China. The taxon has quite smaller, oblong, dark brown to black, three or four-columned conidia with three or four setose appendages. Phylogenetic analyses of combined LSU, SSU, ITS, tef1-α and β-tubulin sequence data revealed that the newly obtained isolate clustered as a monophyletic clade with the species of Triplosphaeria with strong statistical support (98% ML BS/1.0 PP). Based on the morphological comparison and multi-locus phylogeny, we introduce T. guizhouensis as a new species in Triplosphaeria. The description and illustration of the newly discovered taxon, and updated backbone tree of Tetraplosphaeriaceae are provided.